(untitled) (Journal of the College of Basic Education, 2024)
The objective of the current research is to identify the level of job satisfaction among kindergarten teachers, and the researcher relied on the analytical descriptive approach and on building a job satisfaction scale. The job satisfaction scale consists of (32) items, and in front of each paragraph there are five alternatives (it always applies to me, it often applies to me, it sometimes applies to me, it rarely applies to me), and it has weights (5, 4, 3, 2, 1) and higher. The value on the scale is (160) degrees, the lowest score is (32), and the hypothetical average is (96) degrees. When processing the data of the study statistically using the Pearson correlation coefficient, the t-test for two independent samples, the Vachronbach equation, the t-test equation for one value, the results revealed that the research sample had job satisfaction. The research concluded that kindergarten teachers have job satisfaction, as the results came with an arithmetic mean higher than the hypothetical mean of the job satisfaction scale. The research recommended the need to encourage the exchange of experiences between female teachers in governmental and private schools in Riyadh through courses, training lessons or visits, and to continue to strengthen the relations between female teachers and principals because of the great impact that has on the high level of job satisfaction for female teachers, through seminars, lectures and open meetings that It helps in forming social relationships and strengthening bonds of love and friendship between teachers and educators. The research suggested the necessity of conducting a study of self-regulation skills and their relationship to job satisfaction among primary school teachers, and conducting a study of job satisfaction among kindergarten teachers according to the variable of age, years of service, and academic achievement.